{5,5′-Dimethoxy-2,2′-[2,2-dimethylpropane-1,3-diylbis(nitrilomethanylylidene)]diphenolato}palladium(II) - Siti Kamilah Che Soh; Mustaffa Shamsuddin; Mohd Mustaqim Rosli; Hoong-Kun Fun (Acta Crystallographica Section E, 2012)
In the title compound, [Pd(C21H24N2O4)], the complete molecule is generated by crystallographic mirror symmetry with the Pd and three C atoms lying on the mirror plane. The Pd—O and Pd—N distances are 1.9932 (6) and 2.0029 (7) Å, respectively. The dihedral angle between two benzene rings of the ligand is 79.21 (4)°. In the crystal, C—H...O hydrogen bonds link the molecules into layers parallel to the ab plane. These planes are further connected by C—H...O interactions, forming a three-dimensional network.